PERSEPSI MAHASISWA TERHADAP PENGGUNAAN MEDIA PREZI PADA MATA KULIAH ASSESSMENT DI SD - Meria Ultra Gusteti; Sri Novia Martin (Jurnal Riset Pendidikan Dasar Dan Karakter, 2020)
The Covid-19 pandemic affects various aspects of life including education. This has an impact on learning activities that were previously carried out face-to-face to virtual, online or online learning. Online learning is a challenge for both lecturers and students. One of the challenges is the ability of lecturers and students to use technology to support online learning. The selection of methods and the use of various online learning media is carried out so that the learning objectives are maximally achieved. One of the media used to achieve these learning objectives is Prezi media. This media is used during presentations and group discussions. This study aims to determine students' perceptions of the use of Prezi media in the SD assessment course. The research subjects were 32 students of the PGSD study program. This research is a qualitative research. The data were collected using a Likert scale questionnaire. Furthermore, the data were analyzed using three steps, namely data reduction, data presentation and conclusion drawing. The results of this study are that the benefits of Prezi media can be felt and can be used to support students in achieving learning objectives from the aspects of ease of understanding the material, the effectiveness of learning time, attractiveness and usefulness.